Excessive SBP elevation during moderate exercise discriminates patients at high risk of developing left ventricular hypertrophy from hypertensive patients. Issue 6 (June 2018) - Tanaka, Shinya; Masuda, Takashi; Kamada, Yumi; Hamazaki, Nobuaki; Kamiya, Kentaro; Ogura, Misao N.; Maekawa, Emi; Noda, Chiharu; Yamaoka-Tojo, Minako; Ako, Junya
Abstract : Objective: Hypertensive patients show an excessive elevation of SBP during exercise, although optimal blood pressure (BP) control is required to prevent development of left ventricular hypertrophy (LVH). This study examined whether excessive SBP elevation during moderate exercise is associated with new-onset LVH in these patients. Methods: A total of 143 hypertensive patients without LVH whose BP had been maintained below 140/90 mmHg with antihypertensives performed cycle ergometer exercise test at moderate intensity to assess SBP elevation during exercise (ΔSBP). Left ventricular mass index (LVMI) was assessed by echocardiography once a year to identify new-onset LVH. Patients were divided into three groups according to tertiles of ΔSBP. We examined the associations between ΔSBP and new-onset LVH using the Kaplan–Meier method, log-rank test, and Cox regression analysis. Results: The patients (100 men, 65.3 ± 9.1 years) had resting BP of 126 ± 16/75 ± 11 mmHg. New-onset LVH developed in 47 patients (32.9%) within a follow-up period of 2.5 ± 1.6 years. Higher ΔSBP was significantly associated with higher incidence of LVH ( P < 0.001): 12.8, 27.1, and 58.3% in the lowest, middle, and highest tertiles, respectively. In multivariate analysis, ΔSBP was a significant independent determinant of new-onset LVH (hazard ratio for 10 mmHg increase in ΔSBP, 1.45; 95% CI 1.22–1.73; P < 0.001). In comparison with the lowest tertile, the hazard ratios of the middle and highest tertiles for incidence of LVH were 3.16 (95% CI 1.07–9.32) and 6.43 (95% CI 2.35–17.62), respectively. Conclusion: Excessive SBP elevation during moderate exercise can be used to identify hypertensive patients at high risk of developing LVH.